GUIDANCE AND COUNSELING EFFORTS TO IMPROVE STUDENTS' ACADEMIC SELF-EFFICACY: A SYSTEMATIC LITERATURE REVIEW - Wahid, Ahmad; Neviyarni, Neviyarni (Counsenesia Indonesian Journal Of Guidance and Counseling, 2024)
One aspect that is very important and influential on student achievement at school is academic self-efficacy. Because of this urgency, it is expected that students can improve their academic self-efficacy. Low academic self-efficacy will have an adverse impact on a number of aspects that are urgent in student learning activities The focus of this research is to review what services can be provided by guidance and counseling in an effort to alleviate the problem of low student academic self-efficacy. This research is included in the descriptive-analytic type utilizing the systematic literature review method. Literature data collection was obtained from several sources such as Google Scholar, Sinta Ristekbrin, and Elsevier. The number of articles included in this study is 18 articles, which have gone through several stages of screening, so as to obtain literature that supports the research objectives. The results showed that effective efforts that can be made through guidance and counseling to improve academic self-efficacy are the implementation of information services, group guidance services, and group counseling services. The implementation of these services will become more effective and efficient if infiltrated with methods that are more varied and oriented to the characteristics and needs of students.